Att skapa ordning: Den systematiska samlaren - Hagström, Charlotte (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
For a collection to be considered as such, and not appear only as a clutter or jumble of things, it has to be based on some kind of selection and systematisation. The research question of this article is how and why collectors structure, organize and arrange their collections. The research material consists of answers to the directive “Collecting things”, presented by the Mass Observation Archive in 2000, and interviews with two collectors. According to Bowker & Star (2000), to classify is human. However, how things are classified is not inherent or self-evident. Where some use alphabetical order, others take colours as the starting point or origin. What is deemed as a possible structure of a collection is culturally influenced.